The complete mitochondrial genome sequence of Yarkand hare (Lepus yarkandensis). Issue 2 (3rd July 2019) - Huang, Ya-Lin; Chen, Yun-Xia; Guo, Hai-Tao; Xu, Yan-Hong; Liu, Hong-Yi; Liu, Da-Wei
Abstract: We first reported the mitochondrial genome of Lepus yarkandensis . The mitogenome of L. yarkandensis contains 17, 011 base pairs. The overall base composition of complete mitogenome is 28.13% A, 27.67% T, 22.02% C, and 22.17% G, with 44.20% of the GC content. All genes exhibit the typical mitochondrial gene arrangement and transcribing directions. Phylogenetic analysis of 9 Lepus species was performed based on the sequence of cytochrome b gene using the Maximum Likelihood method in MEGA 7.0. The results suggested that L. yarkandensis is closely related to Lepus timidus . The results are helpful to future studies on molecular evolution, population genetics, and wildlife protection of L. yarkandensis .